2022
DOI: 10.21203/rs.3.rs-2208386/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A single amino acid change can alter the specificity of the multi-allelic wheat stem rust resistance locus SR9

Abstract: Most resistance genes thus far isolated from wheat have a very limited number of functional alleles, with the exception of the powdery mildew PM3 resistance locus. Here we report the isolation of most of the alleles at wheat stem rust resistance gene locus SR9, representing the largest multi-allelic rust resistance locus in common wheat. The seven previously reported resistance alleles (Sr9a, Sr9b, Sr9d, Sr9e, Sr9f, Sr9g, and Sr9h) at the locus were characterised using a synergistic strategy. Loss-of-function … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The candidate gene region includes 49 annotated high-con dence genes in Chinese Spring (TraesCS7A01G110400-TraesCS7A01G115200, Supplementary Table 6). The functional annotation of these genes revealed six typical NLR genes (Supplementary Table 6), a gene class frequently associated with disease resistance in plants [32][33][34][35][36][37] .…”
Section: Resultsmentioning
confidence: 99%
“…The candidate gene region includes 49 annotated high-con dence genes in Chinese Spring (TraesCS7A01G110400-TraesCS7A01G115200, Supplementary Table 6). The functional annotation of these genes revealed six typical NLR genes (Supplementary Table 6), a gene class frequently associated with disease resistance in plants [32][33][34][35][36][37] .…”
Section: Resultsmentioning
confidence: 99%
“…Our in-silico structural modelling and analysis did not show an association between the full-length structures or diverse N terminal structures of SR6, SR13, SR21 and temperature sensitivity of resistance. Whereas Sr13 encodes a classic CC-NB-LRR, Sr21 and the SR9 allelic series encode NLR proteins with a unique N terminus comprised of ve helices bundle 49 , and Sr6 falls into the zinc nger BED domain containing R protein encoding gene subset. Interestingly, we observed that all α3 helices from these proteins were the closest unit to their respective LRR domains.…”
Section: Discussionmentioning
confidence: 99%
“…High-resolution mapping of SrTm4 reveals an inversion linked to SrTm4 resistance Most plant disease resistance genes are dominant or partially dominant, but the presence of recessive R genes has also been well documented. However, the nature of wheat stem rust recessive genes remains largely unknown, since all 18 Sr genes cloned so far in wheat and its wild relatives are all dominant or partially dominant (Zhang et al 2022). The recessive nature of SrTm4 and the mesothetic resistant infection types may be indicative of a different mechanism, providing an added incentive to clone this gene.…”
Section: Discussionmentioning
confidence: 99%